HOW TO MANAGE ECOTOURISM FOR EDUCATION PURPOSE: A SWOT ANALYSIS OF SEA TURTLE CONSERVATION TOURISM - Indarwati, Tias Andarini; Sari, Dhita Ayu Permata; Kuntjoro, Sunu; Sifaq, Aghus (International Conference of Business and Social Sciences, 2020)
Ecotourism is defined as responsible travel to natural areas that conserve the environment, sustains the well-being of the local people, and involves interpretation and education for both staff and guests. Taman Beach is a group of cultural tourism destinations and special interests that have sea turtle conservation in Pacitan Regency, East Java, Indonesia. Taman Beach has the potential as an ecotourism destination that can be developed for the benefit of education and preservation of local culture. Various activities have been carried out to increase the attractiveness of ecotourism at Taman Beach or other beaches in Pacitan Regency, but the latest SWOT analysis regarding the condition of sea turtle conservation on Taman Beach has not been carried out specifically. This article aims to describe the swot analysis of the sea turtle conservation tourism at Taman Beach. The method used in this article is a qualitative method that is analyzed descriptively with a SWOT analysis. The results of the analysis show that Taman Beach has some has some strengths, weaknesses, opportunities, and threats. Depending upon swot analysis the relevant strategies to promote Taman Beach as an ecotourism are developing new market, creating or developing a new product, and strengthening the brand image of Taman Beach as turtle conservation education.